Morphogenesis of simple leaves: regulation of leaf size and shape - Rodriguez Virasoro, Ramiro Esteban (2014)
Plants produce new organs throughout their life span. Leaves first initiate as rodlike structures protruding from the shoot apical meristem, while they need to pass through different developmental stages to become the flat organ specialized in photosynthesis. Leaf morphogenesis is an active process regulated by many genes and pathways that can generate organs with a wide variety of sizes and shapes. Important differences in leaf architecture can be seen among different species, but also in single individuals. A key aspect of leaf morphogenesis is the precise control of cell proliferation. Modification or manipulation of this process may lead to leaves with different sizes and shapes, and changes in the organ margins and curvature. Many genes required for leaf development have been identified in Arabidopsis thaliana, and the mechanisms underlying leaf morphogenesis are starting to be unraveled at the molecular level